VoxPL: Programming with the Wisdom of the Crowd - Barowy, Daniel W.; Berger, Emery D.; Goldstein, Daniel G.; Suri, Siddharth (Proceedings of CHI 2017, 2017)
Having a crowd estimate a numeric value is the original inspiration for the notion of “the wisdom of the crowd.” Quality control for such estimated values is challenging because prior, consensus-based approaches for quality control in labeling tasks are not applicable in estimation tasks. We present We present VOXPL, a high-level programming framework that automatically obtains high-quality crowdsourced estimates of values. The VOXPL domain-specific language lets programmers concisely specify complex estimation tasks with a desired level of confidence and budget. VOXPL’s runtime system implements a novel quality control algorithm that automatically computes sample sizes and obtains high-quality estimates from the crowd at low cost. To evaluate VOXPL, we implement four estimation applications, ranging from facial feature recognition to calorie counting. The resulting programs are concise—under 200 lines of code—and obtain high-quality estimates from the crowd quickly and inexpensively.